A Rare Presentation and Management of Forearm Deformity in a Patient with Hereditary Multiple Exostoses: A Case Report. Issue 3 (July 2018) - Agashe, Mandar; Shah, Avi; Parikh, Shital N.
Abstract : Case: We report the case of a patient with a long-standing and progressive forearm deformity, secondary to underlying hereditary multiple exostoses (HME). A salvage surgery was performed with excision of the pathologic parts of the radius and the ulna, followed by the creation of a 1-bone forearm. Conclusion: One of the common manifestations of HME is forearm deformity due to abnormal ossification and osteochondromas that affect the radius and/or the ulna. Progressive deformity can lead to increasing pain, joint instability, limited motion, and functional decline. Neglected or recalcitrant deformities pose a treatment challenge. At 1.5 years after surgery, the patient had a satisfactory outcome with a fully functional, pain-free forearm in a fixed, neutral position.